Challenges of adherence to the therapeutic treatment of the Hiperdia program in the Family Health Strategy: the family doctor as an educator (Research, Society and Development, 2022)
This is a bibliographic research with a qualitative approach and descriptive character that has as its object of study adherence to therapeutic treatment in the Hiperdia program, which aimed to describe the contributions of the family doctor in the process of adherence to the therapeutic treatment of the Hiperdia program in the Health Strategy of the Family. As a methodology, the Virtual Health Library was used, in the LILACS, BDENF, MEDLINE and SCIELO databases, with a time frame from 2015 to 2019. The Hiperdia program is constituted as a strategy: Monitoring hypertensive users and/or diabetic patients, with the functions of linking the patient to the Basic Health Unit and the Family Health Team It is part of the program's proposal to establish links between users and the team and considering their social reality, converging with the perspective of a more integrative care, and towards a more holistic dimension of being. The doctor-patient relationship is of great importance for treatment adherence. The bond assumes a relationship of understanding, support, listening and stimulation of narration. Thus, it encourages a horizontal, trusting relationship, with freedom for the patient to clear up his doubts. It is also concluded that the family doctor's guidelines are necessary with regard to drug and non-drug treatment. Therefore, in addition to recommendations on changes in diet and reduction of sedentary lifestyle, in the treatment of Diabetes and Arterial Hypertension, patients are oriented on the need for changes in lifestyle and the great importance of family support, as a support group.